2017
DOI: 10.1016/j.neuron.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Dopaminergic Neurodegeneration and Impairment of the Autophagy-Lysosomal Pathway in LRRK-Deficient Mice

Abstract: Summary LRRK2 mutations are the most common genetic cause of Parkinson’s disease, but its normal physiological role in the brain is unclear. Here we show that inactivation of LRRK2 and its functional homologue LRRK1 results in earlier mortality and age-dependent, selective neurodegeneration. Loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and noradrenergic neurons in the locus coeruleus is accompanied with increases in apoptosis, whereas the cerebral cortex and cerebellum are unaffect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 51 publications
7
119
1
Order By: Relevance
“…As shown here, knocking out Lrrk2 and its interactor Rab29 had no significant effect on DA pathology related to PD in the aging mouse model, consistent with prior reports of single LRRK2 knockouts (Volta et al, 2015;Kuwahara et al, 2016). However, double knockout of LRRK2 and LRRK1 is reported to cause early mortality and significant DA degeneration highlighting the importance of selectively targeting LRRK2 (Giaime et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…As shown here, knocking out Lrrk2 and its interactor Rab29 had no significant effect on DA pathology related to PD in the aging mouse model, consistent with prior reports of single LRRK2 knockouts (Volta et al, 2015;Kuwahara et al, 2016). However, double knockout of LRRK2 and LRRK1 is reported to cause early mortality and significant DA degeneration highlighting the importance of selectively targeting LRRK2 (Giaime et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Evidence regarding the integrity of the noradrenergic system in transgenic mice models of PD is more scarce but also stresses noradrenergic impairment. Thus, reduced tyrosine hydroxylase positive cells and a-synuclein aggregations in the LC have been demonstrated in PINK1 knockout rats (Grant et al, 2015;Cullen et al, 2018), LRRK, and parkin knockout mice (Von Coelln et al, 2004;Giaime et al, 2017). However, in transgenic mice overexpressing human A53T asynuclein, although having lower NA levels at the level of the striatum, olfactory bulb, and spinal cord, TH positive cells in the LC expressed modest a-synuclein aggregates but remained intact in number (Giasson et al, 2002;Sotiriou et al, 2010).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…What also clearly emerged from these studies is that genetic deletion of LRRK2 does not impact autophagy in the brain. A more recent study, however, revealed that the functional homolog of LRRK2, i.e., LRRK1, might play a compensatory role in LRRK2 KO mice (Giaime et al, 2017). Indeed, although any changes of autophagic markers were found in mice constitutively lacking either LRRK2 or LRRK1, double KO mice showed age-dependent increase of p62 and LC3II levels, reduction of LC3I levels, and AV accumulation, indicating an impairment of autophagy (Giaime et al, 2017).…”
Section: Rodentsmentioning
confidence: 97%